Model of essential employability skills framework for machine operator - Hari Din Nugraha; Deny Poniman Kosasih; Kasda Kasda; As'ari Djohar; Mumu Komaro (Jurnal Pendidikan Vokasi, 2020)
Employability skills are the skills that a person must have to get a job, stay in work, and be able to achieve success in their career. This study aims to develop a model of specific employability skills framework for machine operators. The research design used is the mixed methods, a study that combines the quantitative and qualitative methods and convergent parallel strategy in the data mixing process. The research finding is 14 identified frameworks of employability skills, including (1) basic skills: communicating, listening; (2) self-quality: attendance, collaboration, responsibility, honesty, flexibility, empathy; (3) thinking skills: creativeness, problem-solving; (4) management: self-management, planning; (5) system and technology: production flow system, and mastery of job field concept. Industries demand that basic skills have to be possessed by machine operators to be and self-quality as the priority to recruited as prospective skilled workers. Thinking skills, management, and system and technology are better if developed in their future workplace.